Thermo-physiological comfort of half bleached woven fabrics made from different cotton yarns parameters. Issue 13 (1st December 2022) - Atalie, Desalegn; Gideon, Rotich; Melesse, Getnet; Ferede, Eyasu; Getnet, Frezer; Nibret, Abiyou
ABSTRACT: Thermo-physiological comfort of apparel clothing must be suitable for the wearer both in winter and summer seasons. Poor thermo-physiological properties can lead to discomfort, fluctuation in body temperature, poor sweat management during wear and can affect human health as well as work efficiency. For this reason, optimum thermo-physiological comfort of clothing is a prerequisite by users for any given weather. The aim of this study was to investigate the effect of cotton yarn parameters on the thermo-physiological comfort of woven fabrics. Four types of woven fabrics were developed from cotton yarn with different counts, twist, coefficient of variation of mass (CVm), neps, hairiness, thin places, thick places, strength, and elongation. Yarn samples were produced separately by carding and rotor span before they were woven on an air jet machine with the same settings. Finally, the woven fabrics were finished in a combined finishing treatment process. Thermo-physiological properties of fabrics were measured and analyzed. Statistically analyzed results showed that thermal resistance, thermal conductivity, thermal absorptivity, and air permeability of fabrics had statistically significant change with P values of 0.029, 0.035, 0.005, and 0.000, respectively. Model equations were developed based on the results to predict the comfort of the fabric.